Performance analysis of Dirac video codec with H.264/AVC - Issa, Sinzobakwira; Khalifa, Othman Omran (2010)
In this era of digital communications, video compression has become a necessity and plays an integral role that aids the widespread use of multimedia over the Internet. In the digital world, with the rapid growth of the Internet and the introduction of high-definition media, compression is used to exploit limited storage and transmission capacity as efficiently as possible. H.264/AVC is the latest digital video codec standard. It has proven to be superior to earlier standards in terms of compression ratio, quality, bitrates and error resilience. However unlike Dirac, it requires payment of license / patent fees. The objective of this paper is to implement Dirac video codec(encoder and decoder) based on input test sequences, and compares its performance with H.264/AVC. Analysis has been done on Dirac and H.264 using QCIF video test sequences as input and the results have been recorded graphically for various parameters including compression ratio, bit rate, PSNR and MSE. In these tests, encoding and decoding has been performed for quality factor ranging from 0 to 10 and for lossless compression. Apart from this, comparison between Dirac and H.264’s performance has been implemented at various constant ‘target’ bit rates ranging. The comparative result shows that H.264/AVC outperforms the Dirac codec.